DECISION DESIGN SYSTEM FOR SELECTING PROMOTIONAL MEDIA AT SMA N 1 BANYUMAS USING ANALITYCHAL HIERARCHY PROCESS METHOD - Andoyo, Andreas; Artina, Bekti; Khumaidi, Ahmad (JELTec (Journal of Learning Technology), 2023)
Promotion is currently a very important thing in a business in the company. Competition with other providers of goods and services is the main reason for carrying out promotional activities in a company. Schools as educational service providers need to learn and have initiatives to increase customer (student) satisfaction, because education is a circular process that influences each other and is sustainable. Therefore, an education services marketing strategy is needed to win competition between schools and to increase the acceleration of improving the quality and professionalism of school management. The Decision Support System was created to assist users in making decisions. This research was conducted to create a decision support system for selecting promotional media at SMA N 1 BANYUMAS